(untitled) (Fiep Bulletin - online, 2013)
This work is a spin off of a research that started in 2006 and was delivered in the VI Congresso Luso Brasileiro de História da Educação. Its goal was to see if the teaching of the history of physical education followed a linear historiographical perspective. The collected data allowed a number of other findings that were not in the scope of that research. In the present paper, we try to understand the concept that students of the Physical Education course have about history by analyzing the answers of a survey done with 131 physical education students of a federal university. After na analysis based in the rethoric as well as the cognitive work of Lakoff & Johnson (1980, 1999) we identified that 60,30% of the students perceive history is a dead organism while 39,70% as living organism. Thus, the conceptions of the students about history are grounded in the following ontological metaphor: “History is like an organism”. Grounded in this metaphor, the narrative of physical education hás been working as an epedeictic discourse that praises (keeps alive) or censors (burries) sides and positions about what should be done. It also indicates that history is seen as a determined path which end is only knows by its narrator/cooptator. This conception about history, present in the books that are more spread, is present in the student’s discourse.